2020
DOI: 10.3390/biomedicines8090330
|View full text |Cite
|
Sign up to set email alerts
|

BAY 41-2272 Attenuates CTGF Expression via sGC/cGMP-Independent Pathway in TGFβ1-Activated Hepatic Stellate Cells

Abstract: Activation of hepatic stellate cells (HSCs) is a critical pathogenic feature of liver fibrosis and cirrhosis. BAY 41-2272 is a canonical non-nitric oxide (NO)-based soluble guanylyl cyclase (sGC) stimulator that triggers cyclic guanosine monophosphate (cGMP) signaling for attenuation of fibrotic disorders; however, the impact of BAY 41-2272 on HSC activation remains ill-defined. Transforming growth factor (TGF)β and its downstream connective tissue growth factor (CTGF or cellular communication network factor 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Most in vitro studies on the role of heme on sGC function are focused on examining the role of prior heme oxidation (and loss from H-NOX) on the effectiveness of heme-dependent sGC agonists (Morbidelli et al, 2010;Chen et al, 2020). We attempted to address the NMR-based results shown above by testing whether an oxidant such as ODQ can interfere with the sGC stimulatory activity, after the BAY/sGC β1 complex has been allowed to form.…”
Section: Varying the Timing Of Heme Oxidation: Effect The Sgc Catalyt...mentioning
confidence: 99%
“…Most in vitro studies on the role of heme on sGC function are focused on examining the role of prior heme oxidation (and loss from H-NOX) on the effectiveness of heme-dependent sGC agonists (Morbidelli et al, 2010;Chen et al, 2020). We attempted to address the NMR-based results shown above by testing whether an oxidant such as ODQ can interfere with the sGC stimulatory activity, after the BAY/sGC β1 complex has been allowed to form.…”
Section: Varying the Timing Of Heme Oxidation: Effect The Sgc Catalyt...mentioning
confidence: 99%
“…BAY 41-2272, a soluble guanylate cyclase stimulator not based on NO, touches off cGMP signal to attenuate LF. A unique BAY 41-2272 framework for the inhibition of HSCs stimulation though a non-classical Akt-dependent but sGC/cGMP-independent signal [56] .…”
Section: Other Roles With Smad Signaling Pathwaymentioning
confidence: 99%
“…It has been reported that TGFβ induces the expression of CTGF through Smad and Stat3 signaling pathways in HSCs. In A-HSCs, the pro-fibrotic CTGF is also upregulated and promotes the pathogenetic processes of hepatic fibrosis, including cell proliferation, contractility, migration and ECM production [26]. A-HSCs release CTGF and other pro-fibrogenic factors which drive the deposition of ECM [27].…”
Section: Fibrogenic Cytokinesmentioning
confidence: 99%